Collective redress: The need for new technologies - Hodges, C (Springer Verlag, 2018)
After many years of debate on collective redress, the European Commission has proposed to introduce a representative mechanism to be controlled by public bodies and consumer associations that satisfy certain criteria. However, the Commission has only considered a single mechanism (the litigation-based class or representative action), which is in fact “old technology.” There are several other mechanisms that deliver collective redress—new technologies. The first is the partie civile mechanism in which a civil claim “piggy backs” onto a criminal conviction. The most important mechanisms are “regulatory redress”—where a regulatory authority intervenes and agrees or orders redress to be paid—especially if coupled with an ombudsman scheme (not arbitration-based alternative dispute resolution (ADR) schemes). The regulatory redress mechanism was proposed by the Commission in the revised Consumer Protection Cooperation (CPC) Regulation but what emerged was not ideal. All these mechanisms have recently been evaluated against criteria such as their speed, cost, and ability to deliver effective outcomes. The empirical data clearly demonstrate that the new technologies are better than the old technologies. The new technologies also deliver more functions than the old: not just resolution of a dispute or delivery of redress but also assistance to consumers and traders and the ability to aggregate data on trading issues that is fed back to improve compliance, behaviour, and performance in the market place. This evidence leads to the conclusion that the Commission’s proposals are unlikely to deliver effective collective redress for consumers. The proposed method is out of date technology, and other mechanisms are clearly preferable and should be adopted instead. Member States are permitted to maintain existing collective redress mechanisms. That will lead to considerable confusion and diversity, which does not support an integrated single market. Further, the proposal will lead to a diversity of available mechanisms between Member States and hence confusion and competition between intermediaries—forum shopping. The way forward is for the EU to adopt regulatory redress and consumer ombudsmen, rather than the old fashioned litigation model. The analysis also reveals that the Impact Assessment system has flaws.